ISLAMIC LEADERSHIP PRINCIPLES ON MOSQUES PERFORMANCE IN LAGOS STATE, NIGERIA (International Journal of Islamic Business, 2016)
Islamic leadership principles (ILP) involve the 4Cs models, which are Consciousness of Allah, Competency, Consideration, and Consultation. These principles are derived from the Holy Qurâ€™an and the tradition of Prophet Muhammad (ïº»ï» Ù‘ï»° ï·² ï»‹ï» ï¯¾ï®« Ùˆïº³ï» Ù‘Ù…), guided by the efforts of researchers to provide a philosophical background for leadership. The purpose of this article is to explain the ILP (Islamic leadership principles) on Masjid (Mosque) Performance (MP) in Nigeria. This research utilise quantitative methodology where it engage a cross sectional survey and administers 400 questionnaires to the Masjid leadership in Lagos. The regression results of the constructs of Islamic leadership principles (ILP), show that there are significant and positive relationships between Islamic leadership principles and mosque performance. The finding of this study showed that the relationship between ILP and MP is positive and significant. This showed that when Imams and other leaders of the Masjid demonstrated good attitudes and fairness, the followers would emulate them and consequently increase the performance of the Masjid. It was also found that Imams should meet the perspectives of Shura (mutual consultation) to possess good consultation qualities regarding all important affairs of the Masjid. Imams should possess leaderâ€™s traits such as being visionary, and communicate effectively with the Jamaâ€™ah (congregants) of the Masjid. This means that if the Imams adhere to the findings of this study, there will be more effectiveness and efficiency in mosque performance. For further research this study recommends that monitoring and the training system should focus on strengthening the leadership of the Masjid (Mosque).